Effects of environmental and task related conditions on postural control under concurrent visual feedback - Tasci, Seda; Celik, Huseyin; Kirazci, Sadettin (Human movement science, 2024)
Previous studies have yielded conflicting results on the facilitative effects of concurrent visual feedback (CVFB) on postural control. In addition, these effects have generally been assessed only during a single postural task, and their scope has been limited to training sessions in the acquisition phase but not in the later retention phase. One explanation for these conflicting results is that assessing postural control during a single postural task, such as quiet stance, may not be sufficiently challenging for the postural control system to infer balance abilities. We aimed to address these shortcomings by diversifying postural tasks and environmental conditions and by including acquisition and retention phases in the experiments. Does the provision of CVFB of the instantaneous COP position improve performance on a variety of postural tasks compared to no-CVFB controls? Are the effects of the CVFB retained the following day? Do the observed effect sizes differ in magnitude between the environmental and task conditions under CVFB? Forty healthy young adults were randomly assigned to CVFB and no-CVFB control groups. The subjects performed three postural tasks: quiet, tandem, and single-leg stance, under two environmental conditions based on the stiffness of the supporting ground surface. Seven measures of postural sway, including ellipse area, mean speed, and sample entropy, were examined. The provision of CVFB significantly increased sample entropy and sway-path length of the normalized posturogram. In addition, ellipse area, standard deviation of resultant distance, and range in the anteroposterior direction were significantly reduced in the CVFB group compared to the no-CVFB controls; however, these effects were not retained the following day without the addition of CVFB augmentation. The postural sway measures under CVFB were affected by task and environmental constraints, with varying effect sizes. This study demonstrated environment and task-specific changes in postural sway measures under CVFB, which facilitated postural control in a variety of postural tasks. Providing CVFB significantly increased sample entropy, indicating less regular postural sway. The features of CVFB that attract external attention and reduce cognitive overload are possible explanations for these findings. •Young adults were tested in postural tasks to study sway under various conditions.•Participants were divided into concurrent visual feedback (CVFB) and no CVFB groups.•Environmental and task-related conditions affected sway, with varying effect sizes.•CVFB improves performance on postural control during various postural tasks.•Improvements were not retained the following day without CVFB augmentation.